Perceptions of health professionals about the implementation of the Adequate and Healthy Eating Promotion Program in a municipality of the Minas Gerais: a qualitative study - Juliana Mara Flores Bicalho; Eliete Albano de Azevedo Guimarães; Claudia Di Lorenzo Oliveira; Aline Cristine Souza Lopes (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze the implementation of the Adequate and Healthy Eating Promotion Program in a small municipality in Minas Gerais, from the perspective of health professionals. Methods This research used a qualitative approach, with content analysis of semi-structured interviews conducted with professionals from the Family Health Strategy and the multidisciplinary team involved in the implementation of the Adequate and Healthy Eating Promotion Program in Carmo do Cajuru, Minas Gerais. The Program was developed based on the Instructive Manual: group work methodology for food and nutrition actions in primary health care, derived from the Dietary Guidelines for the Brazilian Population, and lasted approximately five months, with 11 biweekly meetings. The interviews were recorded, transcribed and analyzed thematically. Results Twelve health professionals were interviewed. They highlighted the applicability of the program and its positive impact on their daily practice, but reported challenges for its implementation, such as low participant adherence and work overload. Lack of interprofessional engagement was a significant challenge. Facilitating aspects of implementation included the quality of the teaching materials used and the accessible methodology of the Instructive Manual on which the Program was based. Conclusion The results indicate that interventions based on these tools had positive impacts, according to the perspective of health professionals, promoting improvements in the quality of information on food and nutrition, as well as in the diet of participants. However, the challenges identified need to be addressed together with health service managers, aiming to increase participant adherence and its effectiveness.